2022
DOI: 10.3171/2021.11.peds21497
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of quadrigeminal cistern arachnoid cysts: case series and literature review

Abstract: OBJECTIVE Quadrigeminal cistern arachnoid cysts (QACs) are congenital lesions that can cause pineal region compression and obstructive hydrocephalus when sufficiently large. Management of these cysts is controversial and rates of reintervention are high. Given the limited data on the management of QACs, the authors retrospectively reviewed 20 years of cases managed at their institution and performed a literature review on this topic. METHODS The authors performed a retrospective analysis of patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The mechanism was unclear, but we believed that removing the cyst eventually released (continued) Microsurgical fenestration and excision of the quadrigeminal cyst using the SCIT technique were preferred, considering the clear evidence of cerebellar compression, cyst size, predominant infratentorial extension, and progressive worsening of the symptoms without hydrocephalus findings. 7,10,34 Microsurgery is preferred in type II quadrigeminal cysts without hydrocephalus, as sudden cyst decompression may invoke bleeding in the surrounding fragile neurovascular structures. 6,7,34 Bleeding can be more efficiently controlled with microsurgery than an endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism was unclear, but we believed that removing the cyst eventually released (continued) Microsurgical fenestration and excision of the quadrigeminal cyst using the SCIT technique were preferred, considering the clear evidence of cerebellar compression, cyst size, predominant infratentorial extension, and progressive worsening of the symptoms without hydrocephalus findings. 7,10,34 Microsurgery is preferred in type II quadrigeminal cysts without hydrocephalus, as sudden cyst decompression may invoke bleeding in the surrounding fragile neurovascular structures. 6,7,34 Bleeding can be more efficiently controlled with microsurgery than an endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al [1] retrospectively analyzed 12 patients, with one adult, reported an incidence of 83% of hydrocephalus, and performed the ventricular endoscopic approach using the ETV concurrently in three cases. In addition, they advocated the avoidance of shunt whenever possible and have indicated it in selected cases.…”
Section: Rationale Of Treatmentmentioning
confidence: 99%
“…Arachnoid cysts are uncommon malformations of the subarachnoid space, in which the cerebrospinal fluid (CSF) is arrested into the splitting arachnoid membrane, forming a cyst that could become enlarged, isolated from the rest of the subarachnoid space and ventricles, and compressed the surrounding structures [1,2]. Additionally, other hypotheses have been put forward to explain its origin, such as the ectopic production of the CSF by the cyst wall, a slit-valve mechanism, and the osmotic gradient between the CSF and the cyst fluid [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, some retrospective studies have reported that 86% of patients who refused surgical treatment despite being symptomatic might be recovered clinically without surgical intervention (39). It has been reported that endoscopic techniques such as cyst fenestration and removal via the suboccipital supracerebellar approach, lateral ventricle cystostomy, and third ventricle cystostomy should be preferred as a minimally invasive surgical treatment in the treatment of these cysts and that 78-93% of patients treated with these techniques are independent of a shunt (40,41,42).…”
Section: Treatment Modalitiesmentioning
confidence: 99%